Parallels and contrasts between the ASD-STE Dictionary and the Ontology in FunGramKB - Felices Lago, Ángel; Alameda Hernández, Ángela (Onomázein, 2022)
In this article we intend to offer the results of comparing and matching basic and terminal concepts (and their corresponding lexical units) in FunGramKB with Words (and their corresponding synonyms) in the ASD-STE dictionary and determine whether the way in which this controlled language has been designed draws similarities with the way in which the conceptual information of that knowledge base is built. To provide evidence based on authentic material, we have selected the list of 190 approved verbs in the ASD-STE dictionary: a collection of units complying with the ASD-STE lexical and syntactic restrictions. These verbs are used as a representative sample to be compared with 547 verbal concepts stored in the FunGramKB #EVENT subontology (as basic or terminal concepts). The level of compatibility between both repositories offers four possibilities of conceptual and/or lexical matching at varying degrees: i) direct matching, ii) indirect matching, iii) no matching, or iv) missing. The quantitative results of this analysis may prove that a significant percentage of verbal Words in the ASD-STE dictionary (more than 50%) are directly or indirectly represented in FunGramKB, either as concepts or as lexical units associated with other concepts.